2007
DOI: 10.1007/s00247-007-0431-3
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the plain radiograph “shunt series” in the evaluation of suspected ventriculoperitoneal shunt failure in pediatric patients

Abstract: Children with clinically suspected VP shunt failure should proceed directly to cross-sectional or nuclear imaging, as plain radiographic examinations have low sensitivity and significant false-negative rates for detecting shunt abnormalities in all-comers. Use of the shunt series should be limited to patients who specifically have suspected mechanical causes of shunt failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…Our results show that when evaluating sensi- tivity and specificity of shunt images, one needs to relate to the exact shunt part in question: shunt tubing integrity, valve type and setting, and valve integrity. Regarding shunt tubing, the sensitivity of SXR in our series was relatively higher than previously stated (87%) [3][4][5][6][7][8][9][10]21], possibly because we evaluated only SXR and did not include the entire SS images. However, specificity of SXR was high (100%) [5,9,11,12].…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Our results show that when evaluating sensi- tivity and specificity of shunt images, one needs to relate to the exact shunt part in question: shunt tubing integrity, valve type and setting, and valve integrity. Regarding shunt tubing, the sensitivity of SXR in our series was relatively higher than previously stated (87%) [3][4][5][6][7][8][9][10]21], possibly because we evaluated only SXR and did not include the entire SS images. However, specificity of SXR was high (100%) [5,9,11,12].…”
Section: Discussioncontrasting
confidence: 67%
“…The aim of this study was not to justify SS, CT, or any other imaging. As stated above, the sensitivity of SS to diagnose the cause of shunt malfunction is <30%, and in most cases, a SS is not followed by any surgical revision [3][4][5][6][7][8][9][10]. Thus, SS and cranial imaging should be selectively performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,31 This would be beneficial to the patients´ health even with the increased radiation dose. 24 The three highest scoring imaging techniques are C, B, and H, counting for a 65% of the total scores (table 3). The similarities amongst these images are the use of grid, which reduces the scattered radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The SS comprises overlapping anteroposterior and lateral skull, chest and abdominal radiographs which may need to be repeated if suboptimal imaging is obtained due to patient movement. Desai et al 6 reported that SS has a poor sensitivity and a significant false-negative in the detection of SF and is even less likely to agree with the findings from other imaging modalities (CT, MRI, NMC) than by chance alone. Scout images obtained when planning head CT examinations may provide comparable images to lateral skull radiographs to evaluate the VP shunt catheter location.…”
Section: Commentarymentioning
confidence: 99%